PET engineering plastic with high strength and low temperature toughness and preparation method thereof

By using a three-stage vacuum process to remove moisture in the preparation process of PET engineering plastics, the esterification and polycondensation reaction is promoted, and the problem of poor low-temperature toughness of PET engineering plastics is solved, and the comprehensive performance improvement of high strength, excellent low-temperature toughness and high thermal deformation temperature is achieved.

CN119613927APending Publication Date: 2025-03-14SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411898865.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing PET engineering plastics have poor low temperature toughness, and in the modification process, there are problems such as free water inhibiting esterification and polycondensation, resulting in low molecular weight and poor performance.

Method used

A three-stage vacuum preparation process is adopted, and a vacuum degree of -0.08~-0.1MPa is applied in the feed, melt plasticization and extrusion stages respectively to remove moisture in the raw materials, promote esterification and polycondensation reaction, and improve PET molecular weight and performance.

Benefits of technology

It significantly improves the low-temperature toughness and room-temperature mechanical properties of PET engineering plastics, and at the same time improves the thermal deformation temperature, ensuring the stability and wide application of the material in a low-temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613927A_ABST
    Figure CN119613927A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high-performance material processing, and particularly provides a preparation method of high-strength low-temperature toughness PET (polyethylene terephthalate) engineering plastic, which adopts a three-section vacuum preparation process, and comprises the following steps: respectively applying vacuum degrees of-0.08 to-0.1 MPa in a feeding stage, a melting and plasticizing stage and an extrusion stage; the inventor finds that the process combination can better remove moisture in the raw materials, save the drying process in the PET modification process, save the time cost, prevent degradation of the PET raw materials at high temperature, promote normal operation of esterification condensation polymerization, improve the performance of the product, relatively improve the molecular weight of the PET resin matrix, and improve the quality of the PET resin matrix. The purpose of improving the low-temperature toughness of the modified plastic is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a PET engineering plastic with high strength and low temperature toughness and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) engineering plastics is one of the most active research and development hotspots in the field of PET non-fiber applications in the world today. Especially in recent years, PET has been increasing its share in engineering plastics used in different industries due to its excellent performance, low production cost and high cost performance. Currently, engineering-grade PET is widely used in various load-bearing equipment, automobiles, household appliances and furniture.

[0003] At present, improving the toughness of PET engineering plastics is an important research topic for engineers. From a process perspective, in the production process of traditional PET modified plastics, a vacuum preparation method is often used at the extruder. In the polymerization process of terephthalic acid and ethylene glycol, water as a by-product has a huge impact on the molecular weight of PET, and the molecular weight of polymers is a key factor affecting their mechanical properties. In this context, effectively removing moisture from the raw materials is a prerequisite for the excellent performance of modified resins.

[0004] In terms of PET low-temperature toughness, the low toughness of PET is closely related to its molecular structure and crystallization behavior. First, the large number of benzene ring structures in the PET molecular chain leads to poor flexibility of the molecular chain. Under the action of external force, it cannot absorb impact energy through the movement of the molecular chain. At the same time, due to the weak movement ability of the molecular chain, it is difficult for the molecular chain to be arranged into the lattice during the cooling and crystallization process of PET, resulting in low crystallinity and poor toughness. In recent years, great progress has been made in improving the room-temperature toughness of PET engineering plastics by increasing crystallinity and adding compatible toughening agents, but there are few reports on the improvement of PET toughness at low temperatures. Due to the differences in climate around the world, if PET engineering plastics have poor low-temperature toughness, equipment using PET engineering plastics as component materials in extremely cold areas will experience brittle cracking at low temperatures or brittle failure under external forces, resulting in the scrapping of the entire equipment. Therefore, the improvement of PET engineering plastics low-temperature toughness is a key issue for whether PET engineering plastics can be widely used in the future. The existing patented technology has not improved the low-temperature toughness of PET engineering plastics to a small extent, and the method of adding a large amount of toughening agents is likely to reduce the heat deformation temperature.

[0005] Invention patent CN1136577A proposes that by adding nylon nucleating agent and epoxy resin chain extender to 30 glass fiber reinforced PET engineering plastic, the obtained material has high tensile strength, but the toughness is still very low, only 7.4KJ / m 2 , and no improvement in low temperature toughness is involved.

[0006] Invention patent CN101875759A proposes to use acrylic copolymer toughening agent and SEBS elastomer to toughen glass fiber reinforced PET engineering plastics. The obtained material has good low temperature toughness and the impact strength in low temperature environment reaches 12KJ / m 2 However, the toughening agent content in the material formula is too high, reaching about 20% in the formula system. Too much elastomer toughening agent can easily lead to a decrease in strength and heat resistance temperature. The test results in the patent show that the tensile strength is only about 110MPa, and the heat deformation temperature is as low as 200℃ (1.82MPa).

[0007] Therefore, whether it is possible to provide a PET engineering plastic with high strength and low temperature toughness has become one of the problems that need to be solved urgently in this field. Summary of the invention

[0008] In order to solve the problems in the prior art that PET engineering plastics have poor low-temperature toughness, and that the presence of free water in PET inhibits the forward progress of esterification and polycondensation, resulting in low PET molecular weight and unsatisfactory performance, the present invention provides a preparation method for PET engineering plastics with high strength and low-temperature toughness, adopts a three-stage vacuum preparation process, and applies a vacuum degree of -0.08 to -0.1 MPa in the feeding stage, the melting and plasticizing stage and the extrusion stage respectively. The inventor finds that this process combination can better remove moisture from the raw materials, save the drying process in the PET modification process, save time and cost, and prevent the degradation of PET raw materials at high temperature, promote the normal progress of esterification and polycondensation reaction, improve the performance of the product, and relatively increase the molecular weight of the PET resin base, so as to achieve the purpose of improving the low-temperature toughness of the modified plastic.

[0009] There are precedents in the prior art for using a multi-stage vacuum method to extract small molecules with odor from the reactants, but their application purposes are significantly different from the present application. The present application uses a three-stage vacuum method to extrude PET. The first feeding stage vacuum removes the adsorbed free water in PET. Under the second and third stages of vacuum and high temperature, the esterification polycondensation proceeds in a positive direction, which can help further increase the molecular weight of PET and enhance the performance of the resin. Finally, a reinforced PET engineering plastic with high strength and excellent low-temperature toughness can be obtained. It not only has excellent low-temperature toughness, but also has high mechanical properties at room temperature and has a high heat deformation temperature, and has a large molecular weight. At the same time, the three-stage vacuum process also has an impact on polyurethane and polyester toughening agents such as TPU and TPEE. The by-product of synthesizing such toughening agents is water. The three-stage vacuum can better remove the water in such toughening agents and avoid the hydrolysis of such toughening agents at high temperatures, thereby ensuring that they achieve the expected use effect.

[0010] Specifically, the present invention provides a method for preparing PET engineering plastics with high strength and low temperature toughness, comprising the following steps: 1) Mixing the raw materials of the base resin uniformly to obtain a mixture; 2) introducing glass fiber into a twin-screw extruder, and extruding the mixture obtained in step 1) through the twin-screw extruder to form pellets; The twin-screw extruder is configured to perform three-stage vacuuming, wherein the three-stage vacuuming includes vacuum in the feeding stage, vacuum in the melting and plasticizing stage, and vacuum in the extrusion stage, and the vacuum degree is -0.08 to -0.1 MPa.

[0011] Preferably, the three-stage vacuum extruder has a length-to-diameter ratio of 52-60, a temperature of 240-260° C., and a screw speed of 350-450 r / min.

[0012] The screw length-to-diameter ratio of the three-stage vacuum extruder used in this application is relatively large. The large length-to-diameter ratio increases the retention time of the material in the extruder and has a better effect of removing moisture, thereby promoting the positive polymerization reaction of PET, increasing the molecular weight of the matrix resin, and improving the resin performance.

[0013] Preferably, the glass fiber is selected from one of continuous glass fiber and chopped glass fiber; the fiber diameter of the continuous glass fiber and the chopped glass fiber is 10~14μm, wherein the continuous glass fiber can be fed from the fiber inlet of the twin-screw extruder, and the chopped glass fiber can be added from the side feeding port of the twin-screw extruder.

[0014] Preferably, the raw materials of the matrix resin include 45-80 parts of PET, 2-15 parts of a compatible toughening agent, 0.2-3 parts of a crystallization nucleating agent, and 0.05-0.4 parts of a crystallization accelerator, and the added amount of the glass fiber is 15-45 parts.

[0015] More preferably, the raw materials of the matrix resin include 50-75 parts of PET, 3-8 parts of compatible toughening agent, 0.5-2 parts of crystallization nucleating agent, 0.07-0.3 parts of crystallization accelerator, the added amount of the glass fiber is 20-40 parts, and the intrinsic viscosity of the PET is 0.8-1.5dL / g.

[0016] A smaller amount of crystallization nucleating agent will affect the crystallization nucleation efficiency, while an excessive amount will reduce the toughness of the material; a smaller amount of crystallization accelerator will result in poor plasticization effect, while an excessive amount will reduce the strength of the material, so the above dosage range is selected.

[0017] Preferably, the compatible toughening agent is selected from one or more of thermoplastic polyester elastomer toughening agent (TPEE), thermoplastic polyurethane elastomer toughening agent (TPU) and a product of maleic anhydride grafted TPU or TPEE.

[0018] Preferably, the crystal nucleating agent is a crystal nucleating agent commonly used in commercialized PET engineering plastics, such as SURLYN8920 compounded with talc in a weight ratio of 1:1.

[0019] Preferably, the crystallization accelerator is selected from polyethylene glycol and polyethylene glycol ester.

[0020] The PET engineering plastics prepared by the above method have excellent low-temperature toughness and large molecular weight, high heat deformation temperature, and significantly improved mechanical properties.

[0021] Compared with the prior art, the present invention adopts TPEE and TPU toughening agents, which can greatly improve the low-temperature toughness of PET engineering plastics without damaging the strength and heat deformation temperature of PET engineering plastics. At the same time, the three-stage vacuum process can better remove the moisture in such toughening agents, ensuring the physical properties of such modified additives to achieve the expected effect.

[0022] In summary, the present invention adopts a three-stage vacuum forming process, and the free water adsorbed in PET is removed by vacuum in the first feeding stage. Under the vacuum and high temperature in the second and third stages, the esterification polycondensation proceeds in a positive direction, which can help further increase the molecular weight of PET and enhance the performance of the resin; improve the mechanical properties of PET engineering plastics, increase its molecular weight, and improve its low-temperature toughness while maintaining a relatively high heat deformation temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the positions of the three-stage vacuum on the twin-screw extruder in this application. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.

[0025] In the following Examples 1 to 11 and the comparative example, the PET used is Shanghai Yuanfang CB-608S; the continuous glass fiber is ER13-2000-988A, and the chopped glass fiber is ECS301CL; the acrylate compatible toughening agent is French Arkema AX8900; the TPEE compatible toughening agent is DuPont's Hytrel4056 TPEE, and the maleic anhydride grafted TPEE is ch7563; the crystallization nucleating agent is SURLYN8920 compounded with talc in a weight ratio of 1:1; and the crystallization accelerator is polyethylene glycol PEG 400.

[0026] The raw material composition ratios of Examples 1 to 11 and the comparative example are shown in Table 1.

[0027] Table 1 Raw materials and proportions of PET engineering plastics in Examples 1 to 11 and Comparative Examples (parts by weight) Other substances in the table are selected from antioxidants, lubricants, color powders and other commonly used additives in the field, all of which are commercially available products. The amounts used can be adjusted arbitrarily within the amounts used according to actual uses, and the inventor will not elaborate on them.

[0028] The PET engineering plastics of Examples 1 to 11 were all prepared according to the following method: 1. According to the raw material ratio in Table 1, mix all other materials except glass fiber in a high-speed mixer at a speed of 400~500r / min.

[0029] 2. The mixture is extruded into granules through a twin-screw extruder, during which a three-stage vacuum extrusion process is used (such as Figure 1 As shown in the figure), vacuum is applied to the area behind the feed port, the exhaust port area, and the area before the injection port respectively; glass fibers are introduced at the same time, with continuous glass fibers fed from the fiber feed port and short chopped glass fibers added from the side feed port; The parameters of the three-stage vacuum extrusion process are: extruder aspect ratio 56; temperature: 240-260°C; screw speed: 350-450r / min; vacuum degree: -0.08--0.1 Mpa.

[0030] The PET engineering plastic of the comparative example was prepared in a method substantially the same as that of the above-mentioned Examples 1 to 11, except that the twin-screw extruder did not adopt a three-stage vacuum process, but only adopted a one-stage vacuum extrusion process in the feeding section, and its parameters were: extruder aspect ratio 40; temperature: 240 to 260° C.; screw speed: 350 to 450 r / min; vacuum degree: -0.08 to -0.1 Mpa.

[0031] In Examples 12 to 15, the PET used is Shanghai Yuanfang CB-608S; the continuous glass fiber is ECT5301, and the chopped glass fiber is ECS301CL; the TPEE-type compatible toughening agent is DuPont's Hytrel4056 TPE, and the TPU-type compatible toughening agent is Bayer's TPU 250; the crystallization nucleating agent is SURLYN8920 and talc in a weight ratio of 1:1; the crystallization accelerator is polyethylene glycol ester Uniplex 512.

[0032] The raw material composition ratios of Examples 12 to 15 are shown in Table 2.

[0033] Table 2 Raw materials and proportions of PET engineering plastics in Examples 12 to 15 (parts by weight)

[0034] The preparation method of the engineering plastics of Examples 12 to 15 is the same as the preparation method of the engineering plastics of Examples 1 to 11.

[0035] The performance test results of Examples 1 to 11 and the comparative example are shown in Table 3, and the performance test results of Examples 12 to 15 are shown in Table 4.

[0036] The test method standards are as follows: Tensile strength, ISO 527-2; Flexural strength, ISO 178; Izod notched impact strength, ISO 180 / IU; Heat deflection temperature, ISO 175-1, 2.

[0037] Table 3 Performance test results of PET engineering plastics of Examples 1 to 11 and Comparative Examples

[0038] Table 4 Performance test results of engineering plastics in Examples 12 to 15

[0039] It can be seen from the performance test results shown in Table 3 and Table 4 that the PET engineering plastics prepared by the present invention, due to the addition of the three-stage vacuum process, the moisture in the polyurethane toughening agents such as TPEE and TPU is better removed, thereby avoiding the high-temperature hydrolysis of such polyurethane polymers, ensuring the effect of the toughening agent, and the finally obtained material not only has good strength and toughness at room temperature, but also has high impact strength at low temperature, and has excellent comprehensive properties, and can be widely used in electronic appliances, machinery and automotive equipment used in cold regions.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing PET engineering plastics with high strength and low temperature toughness, characterized in that: The following steps are involved: 1) Mixing the raw materials of the base resin uniformly to obtain a mixture; 2) introducing glass fiber into a twin-screw extruder, and extruding the mixture obtained in step 1) through the twin-screw extruder to form pellets; The twin-screw extruder is configured to have three-stage vacuuming, including vacuuming in the feeding stage, vacuuming in the melting and plasticizing stage, and vacuuming in the extrusion stage, with a vacuum degree of -0.08 to -0.1 MPa; the length-to-diameter ratio of the three-stage vacuuming extruder is 52-60, the temperature is 240 to 260°C, and the screw speed is 350 to 450 r / min.

2. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 1, characterized in that: The glass fiber is selected from one of continuous glass fiber and chopped glass fiber; the fiber diameter of the continuous glass fiber and the chopped glass fiber is 10-14 μm.

3. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 2, characterized in that: The continuous glass fiber is fed from the fiber inlet of the twin-screw extruder, and the chopped glass fiber is added from the side feed port of the twin-screw extruder.

4. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 1, characterized in that: The raw materials of the matrix resin include 45-80 parts of PET, 2-15 parts of compatible toughening agent, 0.2-3 parts of crystallization nucleating agent, 0.05-0.4 parts of crystallization accelerator by weight, and the added amount of the glass fiber is 15-45 parts.

5. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 4, characterized in that: The raw materials of the base resin include 50-75 parts of PET, 3-8 parts of compatible toughening agent, 0.5-2 parts of crystallization nucleating agent, 0.07-0.3 parts of crystallization accelerator by weight, the added amount of the glass fiber is 20-40 parts, and the intrinsic viscosity of the PET is 0.8-1.5dL / g.

6. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 4 or 5, characterized in that: The compatible toughening agent is selected from one or more of thermoplastic polyester elastomer toughening agents, thermoplastic polyurethane elastomer toughening agents, or products of maleic anhydride grafted TPU or TPEE.

7. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 4 or 5, characterized in that: The crystal nucleating agent is selected from SURLYN8920 and talc powder in a weight ratio of 1:

1.

8. The method for preparing PET engineering plastics with high strength and low temperature toughness according to claim 4 or 5, characterized in that: The crystallization accelerator is selected from one of polyethylene glycol and polyethylene glycol ester.

9. PET engineering plastics prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Reinforced polyethylene glycol terephthalate-modified material and preparation method thereof

    CN101875759A

  • Glass fiber reinforced polyester (PET) composite material and its preparing method

    CN1136577A

  • Quickly crystallized polyester engineering plastic and preparation method thereof

    CN101787184A

  • Heat-resistant food container, and manufacturing method for same

    CN103826980A

  • Modified PET engineering plastic and preparation method thereof

    CN114426758A